2018
DOI: 10.1016/j.jphs.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol-loaded nanoemulsion prevents cognitive decline after abdominal surgery in aged rats

Abstract: The maladaptive response of aged microglia to surgery and consequent neuroinflammation plays a key pathogenic role in postoperative cognitive dysfunction (POCD). Here, we assessed the preventive effect of resveratrol (RESV) for POCD in aged rats. The emulsified form of RESV (e-RESV) was selected to improve its oral and brain bioavailability. Animals were assigned to one of four groups: e-RESV (80 mg/kg) versus vehicle treatment by abdominal surgery versus isoflurane anesthesia alone (n = 8 in each group). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Hovens et al (2014) reported that exploratory behavior, but not learning and memory, was significantly correlated with plasma IL-6 levels 24 h following abdominal surgery, and microglial activation in hippocampal CA1 was significantly correlated with the performance of OF, FC, and Y-maze at 43 days after surgery (Hovens et al, 2013). In addition, other studies also found that there was an inverse relationship between hippocampal TNF-α and IL-1β levels, and NOR performance 7 days after abdominal surgery (Kawano et al, 2015;Locatelli et al, 2018). The reason for the negative results of the correlation analysis in the present study was largely due to the fact that hippocampal pro-inflammatory cytokines had almost decreased to baseline after the behavioral tests was completed (Figure 9A), which was further proved by hippocampal TNF-α, IL-6, and IL-1β mRNA levels that decreased to around control levels on day 3 and/or day 7 following surgery ( Figure 10).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Hovens et al (2014) reported that exploratory behavior, but not learning and memory, was significantly correlated with plasma IL-6 levels 24 h following abdominal surgery, and microglial activation in hippocampal CA1 was significantly correlated with the performance of OF, FC, and Y-maze at 43 days after surgery (Hovens et al, 2013). In addition, other studies also found that there was an inverse relationship between hippocampal TNF-α and IL-1β levels, and NOR performance 7 days after abdominal surgery (Kawano et al, 2015;Locatelli et al, 2018). The reason for the negative results of the correlation analysis in the present study was largely due to the fact that hippocampal pro-inflammatory cytokines had almost decreased to baseline after the behavioral tests was completed (Figure 9A), which was further proved by hippocampal TNF-α, IL-6, and IL-1β mRNA levels that decreased to around control levels on day 3 and/or day 7 following surgery ( Figure 10).…”
Section: Discussionmentioning
confidence: 96%
“…The results showed that there were no significant differences in the three pro-inflammatory cytokines between groups (Figure 9A). Some studies reported that there was an inverse relationship between levels of proinflammatory cytokines and behavioral performance after surgery (Kawano et al, 2015;Locatelli et al, 2018). Accordingly, we decided to investigate the correlation between three hippocampal cytokine levels and the integrated memory Z-scores by combinations of different behavioral tests.…”
Section: Hippocampal Inflammation Following Behavioral Tests After Anmentioning
confidence: 99%
“…Decreased expression levels of SIRT1 have been observed in the hippocampus of aged dNCR model mice [ 13 ]. dNCR model mice respond to therapies by upregulating SIRT1 expression in the hippocampus, as shown by a neuroprotective treatment of aged mice with SIRT1 activators [ 14 , 15 ]. Recent reports have shown that SIRT1 is involved in protein quality control, as SIRT1 suppressed aggregation of tau proteins [ 16 ] and HMGB1 transcription [ 17 ] by direct deacetylation regulation.…”
Section: Introductionmentioning
confidence: 99%
“…SIRT1 represents a class III lysine deacetylase that is expressed in neuronal cells and known to preserve the mitochondrial function (Houtkooper, Pirinen, & Auwerx, ). The neuroprotective action of resveratrol has been shown to be through SIRT 1 activation (Locatelli et al, ). Sirtinol, a specific SIRT1 inhibitor, could inhibit this effect (Locatelli et al, ).…”
Section: Resveratrolmentioning
confidence: 99%
“…The neuroprotective action of resveratrol has been shown to be through SIRT 1 activation (Locatelli et al, ). Sirtinol, a specific SIRT1 inhibitor, could inhibit this effect (Locatelli et al, ). SIRT1 may interact with PGC‐1α and therefore performs a significant role in mitochondrial biogenesis (Nemoto, Fergusson, & Finkel, ).…”
Section: Resveratrolmentioning
confidence: 99%